(untitled) (Bioscience Journal, 2016)
Fruit flies are considered important pests of world fruit production, causing significant losses in yield and limiting the free movement of fruit due to the restrictions imposed by importing countries. Thus, the objective of the study was to investigate the infestation rates and faunal analysis to characterize the fruit fly assemblage in an orchard located in Bambuí, MG, Brazil. To this end, samples were taken weekly with fly traps hung in the trees, at a height of about 1.60 m height. Faunal analysis and study of infestation rates were conducted. The captured species were Ceratitis capitata, Anastrepha grandis, A. fraterculus, A. pseudoparallela, A. obliqua, A. dissimilis, A. zenildae, A. sororcula, A. similis, A. aczeli and A. bistrigata. The species varied throughout the studied period, but only C. capitata reached an economic threshold requiring better management of these insects in areas with citrus, acerola and fig. The predominant species was C. capitata.